2002
DOI: 10.1590/s0102-311x2002000300031
|View full text |Cite
|
Sign up to set email alerts
|

Qual seria a fonte de fungos miceliais encontrados em leite humano ordenhado?

Abstract: Studies on the vertical stratification of phlebotomine sandfly fauna were conducted in a non-flooded primary forest at a Tropical Forest Experimental Station of the National Institute of Amazonian Research from October 1998 to March 1999. CDC light traps were placed at one, 10, and 20 meters above ground. A total of 2,859 sandflies were captured, belonging to the Lutzomyia (99.93%) and Brumtomyia (0.07%) genera, represented by 38 species. In the Lutzomyia gender, the most frequent sub-gender was Nyssomyia (43.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…For each month of collection on both trails, the mean abundance and richness of sand flies per trap/night was higher in the canopy than at ground level. This finding corroborates the findings of other Amazonian studies [ 12 , 14 , 16 ]. The canopy provides more plentiful resting sites among leaves and trunks, and offers a greater variety of nocturnal blood-meal sources which may attract sand flies since sand flies are most active at night.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For each month of collection on both trails, the mean abundance and richness of sand flies per trap/night was higher in the canopy than at ground level. This finding corroborates the findings of other Amazonian studies [ 12 , 14 , 16 ]. The canopy provides more plentiful resting sites among leaves and trunks, and offers a greater variety of nocturnal blood-meal sources which may attract sand flies since sand flies are most active at night.…”
Section: Discussionsupporting
confidence: 93%
“…To understand how CL is transmitted in the region, it is necessary to determine ecological parameters such as the composition and diversity of phlebotomine species (with a focus on vectors) and to identify which vertebrate blood meals participate in the maintenance of the Leishmania cycle in forest environments. In rainforests, the distribution of sand fly populations can be influenced by physical, biological and microclimatic conditions that differ between stratification levels [ 14 ]. For example, Lutzomyia davisi is found in abundance both in canopy and at ground level [ 14 , 15 ], but Lutzomyia flaviscutellata tends to be distributed at ground level where it feeds primarily on rodents [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast: A majority of Aspergillus was isolated from this particular site. It should be noted that the Aspergillus glaucus and Aspergillus niger complexes have already been isolated from milk samples [207,208]. Interestingly, four publications reported fungal infections following breast implant surgery, a situation that is not well-known in this field, due to Aspergillus niger [209,210], Paecilomyces variotii [211] and Scedosporium apiospermum [212].…”
Section: Rarely Involved Anatomical Sitesmentioning
confidence: 99%
“…Sand flies (phlebotomines), the vectors of Leishmania , are poor flyers (Dias-Lima et al 2002) that are attracted to lighted surroundings but are usually not found directly on lamps. In periurban areas, street lighting attracts sand flies to small farms or kitchen gardens, where dogs, chickens, and other small animals become the hosts.…”
Section: Leishmaniasismentioning
confidence: 99%